Visual symptoms and control of the Red Palm Weevil (Rhynchophorus ferrugineus) in the Gaza Strip, Palestine - ABDEL FATTAH N. ABD RABOU; EQBAL S. RADWAN (Smujo International, 2017)
Abd Rabou AN, Radwan ES. 2017. Visual symptoms and control of the Red Palm Weevil (Rhynchophorus ferrugineus) in the Gaza Strip, Palestine. Nusantara Bioscience 9: 322-329. The Red Palm Weevil – RPW (Rhynchophorus ferrugineus Olivier) (Coleoptera: Curculionidae) has recently become one of the most destructive pests of Date Palms in the Gaza Strip and the Middle East. It is a serious pest threatening the Date Palm health and production, with the larva is the most destructive stage. The current study aims at introducing the visual symptoms and control techniques of the RPW in the Gaza Strip, Palestine. Field surveys and institutional visits were applied to fulfill the purpose of the study. The current study documented that first local infestation of Date Palm trees with the RPW was discovered in late 2011. The introduction of infected offshoots from Egypt through earth tunnel trade and the ability of the adult RPW to fly long distance and cross borders seem to be main causes of the local infestations with the pest. Different control techniques have been adopted by the responsible parties to combat the RPW; with the integrated pest management (IPM) program was tracked and respected. Finally, the study recommends the cooperation of different parties and authorities to adopt appropriate policies to eliminate the RPW and to support farmers with the necessary pesticides and equipment to control this painful pest.